OHCA (Out-of-Hospital Cardiac Arrest) and CAHP (Cardiac Arrest Hospital Prognosis) scores to predict outcome after in-hospital cardiac arrest: Insight from a multicentric registry. (November 2020) - Chelly, Jonathan; Mpela, Alain-Gil; Jochmans, Sebastien; Brunet, Jennifer; Legriel, Stéphane; Guerin, Laurent; Soummer, Alexis; Persichini, Romain; Sauneuf, Bertrand; Pham, Taí; Hullin, Thomas; Pourcine, Franck; et al.
Abstract: Aim: We assessed the ability of the Out-of-Hospital Cardiac Arrest (OHCA) and the Cardiac Arrest Hospital Prognosis (CAHP) scores to predict neurological outcome following in-hospital cardiac arrest (IHCA). Methods: Retrospective review of a seven-year French multicentric database including ten intensive care units. Primary endpoint was the outcome at hospital discharge using the Cerebral Performance Category score (CPC) in all IHCA patients. OHCA and CAHP scores, sequential organ failure assessment (SOFA) score and the simplified acute physiological score 2 (SAPS-2) were compared using area under ROC curves (AUROC) and Delong tests. Results: Among 381 included patients, 125 (33%) were discharged alive with favourable outcome (CPC 1–2). Among 256 patients (77%) with unfavourable outcome (CPC 3–5), 10 were discharged alive with CPC 3 (4%), 130 died from withdrawal of life sustaining therapies because of severe neurological impairment (51%), 107 died from multiorgan failure (42%) and 9 died after discharge from complications and comorbidities (3%). OHCA and CAHP scores were independently associated with unfavourable outcome. The AUROCs to predict unfavourable outcome for OHCA, CAHP, SAPS-2 and SOFA scores were 0.76 [0.70–0.80], 0.74 [0.69–0.79], 0.72 [0.67–0.77], and 0.69 [0.64–0.74] respectively, with a significant difference observed only between OHCA and SOFA scores AUROCs (p = 0.04). Conclusion: In parallel with CAHP score, OHCA score could be used to early predict outcome at hospital discharge after IHCA. However, prediction accuracy for all scores remains modest, suggesting the use of other dedicated means to early predict IHCA patients' outcome.